Pengelolaan Klien dengan Diare Disertai Dehidrasi Berbasis Evidence Nursing di Ruang Dahlia RS Murni Teguh Sudirman - Risma Tio Siahaan; Dior Manta Tambunan (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Diarrhea is a disease with signs of changes in the shape and consistency of soft or liquid stools and an increase in the frequency of defecation more than 5 times while for infants the frequency is more than 3 times. The existence of this study determines the effect of zinc administration on reducing the frequency of liquid stools and dehydration in children. With the design method or design in this study is to use a case study. Case study is one type of qualitative method in research that wants to explore a particular case in more depth by involving the collection of various sources of information.